Nilai-Nilai Pendidikan Krakter dalam Novel Negeri 5 Menara - Kulsum, Ummu (AL-FIKRAH: Jurnal Studi Ilmu Pendidikan dan Keislaman, 2018)
Novel is one type of literary work that is very useful, through moral values that are presented can beused and learned by the reader.The Researcher conducted this research to identify and describe the values of character education thatappears in the land of five towers novel based on Thomas Lickona’s Theory. It is a content analysis byusing qualitative approach. Therefore, to collect the data that concerns with the values of charactereducation, the researcher uses observation text.The result of this research shows that the values of character education in this novel concern therelation between parents and children, attitude toward friends, teachers or others. Those values ofcharacter education area delivered indirectly. So, the story and the attitudes of the figures areinterpreted by the researcher to describe the values of character education dealing with the theory ofThomas Lickhona.Based on the result of this research, it is suggested to the readers of novel to understand the values ofcharacter education in the novel. So, they can learn and adopt that values of character education intheir life.